Guest Editorial Vol3 no1 - Jennifer Davidson (Scottish Journal of Residential Child Care)
As the new director of the Scottish Institute for Residential Child Care (SIRCC), and being new to the Scottish social policy context, I have had the opportunity over these last six months to view the situation of residential child care from a different perspective. Having formerly worked professionally in both Canada and the USA, I naturally find myself comparing what I know of child care policy, and the role of the residential child care profession from one country to the next. No longer quite so new, I would like to share with you some of my reflections and impressions of the Scottish residential child care situation from that initial perspective, including a mixture of both my commendations and concerns.